ANTIBACTERIAL ACTIVITY OF FOOT SPRAY OF TELANG FLOWER EXTRACT AND COFFEE GROUNDS - Susilo Yulianto; Miftaqul Jannah; Makhabbah Jamilatun (Journal of Vocational Health Studies, 2025)
Background: Foot odor is a problem that often occurs, one of the causes being the Staphylococcus aureus bacteria which contaminates sweaty feet and dirty shoes. Foot spray can be used to reduce foot odor. Telang flowers (butterfly pea) and coffee grounds can be formulated in foot spray to reduce foot odor because they have a distinctive aroma and contain flavonoid compounds as antibacterials. Purpose: This research aims to determine the antibacterial activity of foot spray using telang flower extract and coffee grounds against Staphylococcus aureus. Method: The research was conducted using the disc diffusion method. Foot spray was made in three formulas with varying concentrations of telang flowers and coffee grounds, namely I (0.5 : 0.125), II (1 : 0.25), and III (2 : 0.50). Result: The test results of three formulas showed yellow, orange and brownish purple colors, a distinctive odor of menthol, pH 4.54 - 4.56, viscosity 4.00 – 6.00 Cp and dry time 1 minute 1 second – 1 minute 53 seconds. The antibacterial activity test showed that foot spray had antibacterial activity against Staphylococcus aureus with the diameter of the inhibition zone in Formulas I and II in the medium category, while in III it was in the strong category. This shows that the higher the concentration of telang flowers and coffee grounds, the greater the antibacterial activity. Conclusion: Foot spray made from telang flower extract and coffee grounds could reduce foot odor by inhibiting the growth of Staphylococcus aureus bacteria.